Excess DHA Induces Liver Injury via Lipid Peroxidation and Gut Microbiota-Derived Lipopolysaccharide in Zebrafish - Ding, Qianwen; Hao, Qiang; Zhang, Qingshuang; Yang, Yalin; Olsen, Rolf Erik; Ringø, Einar; Ran, Chao; Zhang, Zhen; Zhou, Zhigang (Frontiers in Nutrition, 2022)
Being highly unsaturated, n-3 long-chain polyunsaturated fatty acids (LC-PUFAs) are prone to lipid peroxidation. In this study, zebrafish were fed with low-fat diet (LFD), high-fat diet (HFD), or 2% DHA-supplemented HFD (HFDHA2.0). To study the possible negative effects of the high level of dietary DHA, growth rates, blood chemistry, liver histology, hepatic oxidative stress, apoptosis, and inflammatory processes were assessed. The cell studies were used to quantify the effects of DHA and antioxidant on cellular lipid peroxidation and viability. The possible interaction between gut microbiota and zebrafish host was evaluated in vitro. HFDHA2.0 had no effect on hepatic lipid level but induced liver injury, oxidative stress, and hepatocellular apoptosis, including intrinsic and death receptor-induced apoptosis. Besides, the inclusion of 2% DHA in HFD increased the abundance of Proteobacteria in gut microbiota and serum endotoxin level. In the zebrafish liver cell model, DHA activated intrinsic apoptosis while the antioxidant 4-hydroxy-Tempo (tempo) inhibited the pro-apoptotic negative effects of DHA. The apoptosis induced by lipopolysaccharide (LPS) was unaffected by the addition of tempo. In conclusion, the excess DHA supplementation generates hepatocellular apoptosis-related injury to the liver. The processes might propagate along at least two routes, involving lipid peroxidation and gut microbiota-generated LPS.